Pengaruh Financial Distress,Intensitas Modal,Leverage, Dan Profitabilitas Terhadap Konservatisme Akuntansi Pada Perusahaan Industri Dasar Dan Kimia - Ruth Citra Lumbantobing; Namira Ufrida Rahmi; Nurhetty Nababan; Debora Sinaga (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The aim of the researchers conduct research to examine how the influence of financial distress, leverage, capital intensity, and profitability on accounting conservatism. The population of 79 companies and 90 samples has been multiplied by three years, and uses documentation data with purposive sampling technique with the results of financial reports from the IDX. Data hypothesis testing was carried out using the classical assumption test. The coefficient of determination was obtained Adjusted R2 0.107, where the variation of the accounting conservatism variable described as Financial Distress, Leverage, Capital Intensity, and Profitability was 10.7% and the other independent variables were 89.3%. The results said: (1) there is no and not significant effect on Financial Distress, Capital Intensity, Leverage on accounting conservatism. (2) It has a significant effect on Profitability on accounting conservatism. (3) It has a significant effect on Financial Distress, Capital Intensity, Leverage and Profitability. simultaneous on accountancy conservatism. Keywords : Financial Distress, Capital Intensity, Leverage, Profitability,Accounting Conervatism